Potensi Zat Warna dari Ekstrak Etanol Kayu Sappang Sebagai KalorimetriAnion - Nurmala Sari; Rachma Rachma; Santi Santi (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2017)
Dye from Sappang Tree has been isolated using ethanol as a solvent. Braziline is one of the chemical compound found in the ethanol extract. The Compound can be used as anion calorimethric due to their active sites of hydroxyl and chromophore groups. Dyes from sappang tree has been tested on 10 g of several types of saturated anions (carbonate, sulfate, phosphate, cyanide, acetate, borax, nitrite, chloride, bromide, and iodide). The results of the tests show that the color of the dye from changes in carbonate, phosphate, cyanide, acetate, nitrite, and hydroxyl. Spectrophotometer UV/Vis is used to detect the limit of cyanide anion. Metanol and acetone show positive results on the dye in cyanide anion. Detection limit of braziline is 3x10-4 M. By addition of cyanide anion, the dye has detection limit at 1x10-4 M.